2015
DOI: 10.15405/ejsbs.171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Students’ Agency and Development of Ownership in a Collaborative Playmaking Project

Abstract: In drama education theories of agency and ownership are implicit, as active participation is a central condition of drama action. In this article a teacher-researcher examines students' individual and collective agency in collaboration during one playmaking project with an international group of 13-14 year-old students. Research question: How does students' agency develop and ownership strengthen in the collective teacher-student collaboration process during the playmaking project? The chronological and narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This process is supported by PAR, but also through dialogical and enquiry-based pedagogical methods of group work or social learning. During such learning processes, students' agency and its emergence in relation to context and questions of the day is a significant outcome (Lehtonen, 2015). We saw this in the Alice case where students became active agents in supporting farmers in the local agroecological system through their engagement in codesigned productive demonstration site activity.…”
Section: Expanded Ecosystem Development Via Relational Agencymentioning
confidence: 97%
“…This process is supported by PAR, but also through dialogical and enquiry-based pedagogical methods of group work or social learning. During such learning processes, students' agency and its emergence in relation to context and questions of the day is a significant outcome (Lehtonen, 2015). We saw this in the Alice case where students became active agents in supporting farmers in the local agroecological system through their engagement in codesigned productive demonstration site activity.…”
Section: Expanded Ecosystem Development Via Relational Agencymentioning
confidence: 97%
“…Efforts to develop student agency in regard to sustainability issues have included youth-led action projects focused on individual and collaborative change in both formal and informal educational contexts (e.g., Trott, 2020). In regard to the evaluation of student agency, a questionnaire tool that has been developed is described by Code (2020) and a number of qualitative research to evaluate students agency have been reported (e.g., Lehtonen, 2015).…”
Section: Student Agency and Activismmentioning
confidence: 99%
“…Evocative images and ideas are reflected in artistic action, and transformed into artistic products or performances (Lehtonen 2013). When there is an open space for expression, humour and dialogue, even social transformation can happen-resistance can be transformed into active agency (Rainio 2008;Lehtonen 2015a).…”
Section: Art-based Learningmentioning
confidence: 99%